Decorin, erythroblastic leukaemia viral oncogene homologue B4 and signal transducer and activator of transcription 3 regulation of semaphorin 3A in central nervous system scar tissue - Minor, Kenneth H. (Oxford University Press, 2011)
Scar tissue at sites of traumatic injury in the adult central nervous system presents a combined physical and molecular impediment to axon regeneration. Of multiple known central nervous system scar associated axon growth inhibitors, semaphorin 3A has been shown to be strongly expressed by invading leptomeningeal fibroblasts. We have previously demonstrated that infusion of the small leucine-rich proteoglycan decorin results in major suppression of several growth inhibitory chondroitin sulphate proteoglycans and growth of adult sensory axons across acute spinal cord injuries. Furthermore, decorin treatment of leptomeningeal fibroblasts significantly increases their ability to support neurite growth of co-cultured adult dorsal root ganglion neurons. In the present study we show that decorin has the ability to suppress semaphorin 3A expression within adult rat cerebral cortex scar tissue and in primary leptomeningeal fibroblasts in vitro. Infusion of decorin core protein for eight days resulted in a significant reduction of semaphorin 3A messenger RNA expression within injury sites compared with saline-treated control animals. Both in situ hybridization and immunostaining confirmed that semaphorin 3A messenger RNA expression and protein levels are significantly reduced in decorin-treated animals. Similarly, decorin treatment decreased the expression of semaphorin 3A messenger RNA in cultured rat leptomeningeal fibroblasts compared with untreated cells. Mechanistic studies revealed that decorin-mediated suppression of semaphorin 3A critically depends on erythroblastic leukaemia viral oncogene homologue B4 and signal transducer and activator of transcription 3 function. Collectively, our studies show that in addition to suppressing the levels of inhibitory chondroitin sulphate proteoglycans, decorin has the ability to suppress semaphorin 3A in the injured central nervous system. Our findings provide further evidence for the use of decorin as a potential therapy for promoting axonal growth and repair in the injured adult mammalian brain and spinal cord.